MELIPATGANDAKAN KEMAMPUAN MEMBACA ANAK USIA DINI DENGAN PERMAINAN "SMART JUMP" - MG. Budi Susanti; Rahmat Mulyono (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This study aims to analyze and find out how to multiply children's reading skills at an early age with the "smart jump" game. This research also uses a qualitative descriptive approach with the case study method. The subjects in this study were all students, parents of students and teachers. Collecting data in this study will use several methods, namely observation methods, interview methods, and documentation methods. The technique to be used in this research is to analyze the data with details of data reduction, data presentation, and conclusion. The validity of the data is carried out to explain the data by using source triangulation. From the results of the study it was found that with the smart jump game all students at an early age can double their reading ability. In the smart jump game, all students at an early age are motivated to be able to read. All children at an early age are invited to multiply their reading abilities with fun playing methods, so that all children at an early age will find it easier to multiply their reading abilities.